2022
DOI: 10.3389/fimmu.2022.816433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LncRNA XIST on Immune Cells of Primary Biliary Cholangitis

Abstract: ObjectivePrimary biliary cholangitis (PBC) is an autoimmune disease with significant gender difference. X chromosome inactivation (XCI) plays important roles in susceptibility to diseases between genders. This work focuses on the differences of LncRNA XIST in several defined immune cells populations as well as its effects on naive CD4+ T cells proliferation and differentiation in patients with PBC.MethodsNKs, B cells, CD4+ T, and CD8+ T cells were separated by MicroBeads from peripheral blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…29,30 She et al reported that high expression of the lncRNA XIST can stimulate the proliferation and differentiation of naive CD4 + T cells in female patients with primary biliary cholangitis (an autoimmune disease that predominantly affects females). 31 Therefore, similar to primary biliary cholangitis, XIST may promote the increase, overactivation, and differentiation of CD4 + T cells, leading to immune dysregulation and tissue damage in SLE. A limitation of this study is that we did not isolate NK cells and only detected the expression of XIST in the remaining cells (including NK cells and other types of immune cells), which showed no difference between SLE patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 She et al reported that high expression of the lncRNA XIST can stimulate the proliferation and differentiation of naive CD4 + T cells in female patients with primary biliary cholangitis (an autoimmune disease that predominantly affects females). 31 Therefore, similar to primary biliary cholangitis, XIST may promote the increase, overactivation, and differentiation of CD4 + T cells, leading to immune dysregulation and tissue damage in SLE. A limitation of this study is that we did not isolate NK cells and only detected the expression of XIST in the remaining cells (including NK cells and other types of immune cells), which showed no difference between SLE patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2013) wrote in his doctoral dissertation that the lncRNA AK053349 was increased in PBMC of PBC patients and positively correlated with the Mayo risk score, emphasizing its potential relevance to the pathogenesis of PBC and worthy of further study (Zhang et al, 2013). Another recent domestic study (She, 2020) found that the expression level of lncRNA XIST in NK cells and CD4 + T lymphocytes of PBC patients was significantly higher than that of healthy controls, and could be clearly located in the nucleus. The high expression of lncRNA XIST in Naïve CD4 + T cells of PBC patients can promote the proliferation of Naïve CD4 + T cells, stimulate the secretion of IFN-γ, IL-17, TGF-β and ROR-γ T cells, and increase the proportion of Th1 and Th7 cells, which led to the occurrence of PBC.…”
Section: Long Non-coding Rna and Primary Biliary Cholangitis Expressi...mentioning
confidence: 94%
“…6C), suggesting differential V(D)J recombination. Moreover, some of these genes have been connected with autoimmune disease (51), of which aberrant Xist is known to play a pivotal role (52)(53)(54). Overall, when comparing Xist positive cells to Xist negative cells in males from infected mothers, Xist positive cells downregulate multiple genes necessary for B cell function, such as Cd79a, Cd79b, Ebf1, Rag1, and Cd74 (Fig.…”
Section: Elevated Xist Levels Impair Bcr Expressionmentioning
confidence: 99%